Decreased expression of LEF1 caused defective decidualization by inhibiting IL-11 expression in patients with adenomyosis - Jingru Duan; Xiaowei Zhou; Hanfei Zhu; Mingjuan Zhou; Mengyu Liu; Yan Zhou; Wenzhu Li; Bufang Xu; Aijun Zhang (Molecular Medicine)
Abstract Reduced lymphoid enhancer-binding factor 1 (LEF1) expression in patients with adenomyosis during the mid-secretory phase leads to impaired endometrial receptivity, affecting embryo implantation. This study investigated the molecular mechanisms underlying reduced endometrial receptivity in 25 adenomyosis patients and 25 controls. Functional experiments were conducted using human endometrial stromal cells (HESCs) and TERT-immortalized HESCs(T-HESCs), with final validation performed using a mouse model. Western blot and quantitative real-time polymerase chain reaction (RT-qPCR) analyses revealed that patients with adenomyosis showed a marked decrease in LEF1 expression in the stromal cells of the endometrium during the mid-secretory phase. In vitro experiments demonstrated that LEF1 knockdown in stromal cells led to impaired decidualization. Transcriptome sequencing, dual-luciferase reporter assays, and chromatin immunoprecipitation (ChIP) experiments showed that LEF1 could bind to the promoter region of interleukin (IL)-11 and promote its transcription, and IL-11 expression was also found to be downregulated in adenomyosis patients. Overexpression of IL-11 rescued the impaired decidualization caused by decreased LEF1 expression. In the in vitro co-culture model, LEF1/IL-11 knockdown led to a reduction in embryo implantation area, which was partially restored upon IL-11 overexpression. In the adenomyosis mouse model, we observed a decrease in LEF1 expression and a reduction in implantation sites compared to control mice, accompanied by impaired decidualization and receptivity. Notably, supplementation with IL-11 restored the number of implantation sites. The decrease in fertility due to reduced endometrial receptivity in adenomyosis patients is a significant clinical issue in assisted reproductive technology. This research provides insights into one potential molecular mechanism underlying this decreased receptivity, with a specific focus on the reduced expression of LEF1 in the endometrial stromal cells during the mid-secretory phase in adenomyosis patients. Our findings offer new perspectives for clinical strategies to improve endometrial receptivity in patients with adenomyosis, potentially enhancing their chances of successful pregnancy.